Lehr- und Lernziele im postgymnasialen Fremdsprachenunterricht in Polen - Ciepielewska, Luiza (Glottodidactica, 2006)
Today’s language politics assumes that every citizen should habe a good command of a least two foreign languages. There are three main teaching goals connected with learning foreign languages: pargmatic, cognitive and affective. In the present paper all of three goals haev been in the context of over-secondary school education in Poland.